PENGARUH TRANSFER OF TRAINING, MOTIVASI KERJA, SERVANT LEADERSHIP TERHADAP KINERJA KARYAWAN (Studi Kasus Pada Kopistudio24 Sigura-gura Malang) - Cellyn Elloise Vorringga; Budi Wahono; M. Ridwan Basalamah (UNIVERSITAS ISLAM MALANG, 2020)
AbstractThis study aims to describe the Transfer Of Training, Work Motivation, Servant Leadesrhip employee performance of the Kopistudio24 Sigura-gura Malang, both partially and simultaneously. This research uses explanative research types with quantitative approaches. The population in this study were employees who worked. Samples taken were 38 respondents. The sampling technique used is total sampling. Data were analyzed using multiple linear regression analysis processed with spss 16.0 software. The data collection method used was a questionnaire. The results showed that Transfer of training, Work Motivation, Servant Leadership the effect was significant on employee performance. Transfer Of Training, has a significant effect on employee performance, work motivation has a significant effect on employee performance, Servant Leadership has a significant effect on employee performance. Transfer Of Training, Work Motivation, Servant Leadership Simultaneous effect on employee performance on the kopistudio24 sigura-gura Malang.Keywords:Transfer Of Training, Work Motivation, Servant Leadership, Employee Performance